Script for an Interactive Educational Video to Improve High School Students’ Expressive and Gestural Skills - Salsa Billa Oktaria; Dwi Kusumawardani; Deden Haerudin (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Theater learning in high school plays an important role in developing students' creativity, confidence, communication, and performance skills. However, students often experience difficulties in displaying natural facial expressions and meaningful body gestures because learning is still dominated by verbal explanation and direct practice without sufficient visual media support. This study aims to describe students' initial expressive and gestural abilities, identify their learning needs, and design an interactive educational video script to support theater learning. This research used a descriptive qualitative method focusing on the analysis and design stages of media development. The research subjects were Grade XI high school students involved in Cultural Arts, particularly theater arts learning. Data were collected through observation, interviews with teachers and students, and documentation studies. The data were analyzed descriptively to formulate the needs and structure of the proposed learning media. The results show that students tend to appear rigid, lack confidence, and have difficulty expressing emotions and gestures according to character demands. The discussion indicates that interactive video media can provide concrete, repeatable, and engaging examples through expression demonstrations, gesture analysis, practice pauses, quizzes, and self-evaluation activities. In conclusion, the designed interactive educational video has strong potential to support more active, contextual, and student-centered theater learning.